Student Perceptions of Fee Policies in Veterinary Medicine: An Ethical and Professional Identity Framework - Aysun Gültekin; Pınar Ayvazoğlu-Demir (Veterinary Sciences, 2026)
This study was conducted to examine the perceptions and attitudes of final-year veterinary students regarding the Official Minimum Fee Schedule established for veterinarians in Türkiye, within a multidimensional framework. The research was conducted with a total of 216 final-year students enrolled in veterinary faculties in Türkiye. Data were collected using a questionnaire consisting of Likert-type items. The construct validity of the scale was assessed using Exploratory Factor Analysis (EFA), and its reliability was measured using Cronbach’s alpha coefficients. The study found that the majority of students considered providing services below the official minimum fee schedule to be ethically inappropriate and reported that professional organizations play an important regulatory and supervisory role in this regard. In terms of demographic variables, no statistically significant differences were found in factor scores based on gender, income level, university, level of education, or internship experience. However, significant differences were identified in the dimensions of regulatory–deontological attitudes and price transparency based on place of residence. In conclusion, attitudes toward the minimum fee schedule in veterinary medicine are shaped not only by legal knowledge but also by ethical values, professional socialization processes, and institutional norms. These findings highlight the importance of addressing fee policies in veterinary education together with their ethical and professional dimensions, as well as strengthening the awareness-raising role of professional organizations.